The FlgN chaperone activates the Na+-driven engine of the Salmonella flagellar protein export apparatus - Tohru Minamino (Nature Portfolio, 2021)
Minamino et al. report that the bacterial FlgN chaperone acts as a switch to activate a backup mechanism for H+-coupled flagellar protein export by interacting with FlhAC to activate the Na+-driven export engine. The proposed mechanism helps to explain how bacteria can maintain flagellar protein export when the ATPase complex export machinery becomes non-functional.